2003
DOI: 10.1128/jcm.41.6.2700-2702.2003
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Chlamydia trachomatis Serovars Associated with Urogenital Infections in Females in New Delhi, India

Abstract: Screening for Chlamydia trachomatis was done for 280 endocervical swab samples by PCR specific for endogenous plasmid. Age dependency was seen in symptomatic patients, with a high chlamydial prevalence rate (28%) found in younger women. Genotyping by restriction fragment length polymorphism analysis of omp1 PCR-positive samples showed serovars D, E, and F to be the most prevalent.Chlamydia trachomatis is a major cause of sexually transmitted disease (16). Serovars D to K are chiefly responsible for urogenital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
38
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 19 publications
10
38
2
Order By: Relevance
“…The GST-CPAF fusion protein was significantly recognized by the pooled positive sera at a dilution of 1:12,500, CT795 and CT089 at 1:2,500, and CT147, CT226, CT694, and various MOMPs at 1:500, demonstrating that CPAF, CT795, and CT089 are more immunodominant than MOMP regardless of the types of MOMPs analyzed. Comparing the nine MOMPs, higher ODs were obtained with MOMPs from serovars B, Ba, D, E, and L2, all of which belong to the C. trachomatis subspecies B complex, suggesting that the 15 patients were predominantly infected with B complex serovars, most likely serovars D and E, in agreement with the epidemiological finding that both serovars D and E are among the most prevalent C. trachomatis serotypes in individuals with sexually transmitted chlamydial infections (3,9,29,30,49). The GSTalone control was not significantly recognized at any dilution.…”
Section: Resultssupporting
confidence: 73%
“…The GST-CPAF fusion protein was significantly recognized by the pooled positive sera at a dilution of 1:12,500, CT795 and CT089 at 1:2,500, and CT147, CT226, CT694, and various MOMPs at 1:500, demonstrating that CPAF, CT795, and CT089 are more immunodominant than MOMP regardless of the types of MOMPs analyzed. Comparing the nine MOMPs, higher ODs were obtained with MOMPs from serovars B, Ba, D, E, and L2, all of which belong to the C. trachomatis subspecies B complex, suggesting that the 15 patients were predominantly infected with B complex serovars, most likely serovars D and E, in agreement with the epidemiological finding that both serovars D and E are among the most prevalent C. trachomatis serotypes in individuals with sexually transmitted chlamydial infections (3,9,29,30,49). The GSTalone control was not significantly recognized at any dilution.…”
Section: Resultssupporting
confidence: 73%
“…Compared to serotyping, the genotyping methods are more sensitive and specific for C. trachomatis serovar identification (Molano et al, 2004). Many studies have shown the feasibility of deducing the serotypes of C. trachomatis clinical isolates using PCR-based RFLP or sequencing of the amplified omp1 gene that encodes the MOMP, the main surface antigen of C. trachomatis (Ikehata et al, 2000; Lysén et al, 2004;Ngandjio et al, 2003Ngandjio et al, , 2004Singh et al, 2003). The omp1 gene exhibits extensive DNA sequence variation in four discrete regions, termed variable segments (VS1-4) (Stephens et al, 1987;Yuan et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these studies, the prevalence of C. trachomatis among asymptomatic women has consistently been reported as being low. Recently, Singh et al found that 28% of symptomatic young women in New Delhi had C. trachomatis infections when tested with a homebrew PCR (21). Whereas in a population-based study using Amplicor PCR, the prevalence of genital chlamydial infection was reported to be 1.1% in men and women (6).…”
Section: Discussionmentioning
confidence: 99%